La Disposition préliminaire du Code civil du Québec, le droit commun et les principes généraux du droit - Glenn, H. (Les Cahiers de droit, 2005)
The Preliminary Provision of the Civil Code of Québec refers to the concept of jus commune. Yet to just which jus commune is it referring ? The author reviews the historic multiplicity of jura communia in Europe, including the jus commune, the common law and the general law of France. The latter has become transnational in character with the French Civil Code as an important contemporary element, but also including the general principles of law. As such, the Civil code should thus take its place within the framework of a much broader transnational legal tradition.